Lenin through the eyes of the world. Letters and comments from abroad. Transl.: from the Russian. [Comp. by K.F. Bogdanova and A.P. Yakushina (Jakušina)]. Introd. by V.V. Anikeyev (Anikeev) (Progress, 1969)
With ills, index and prt. Original title: Pis'ma V.I. Leninu iz-za rubeža.